The Melanistic northern red muntjac (Muntiacus vaginalis) in Nilgiris, Tamil Nadu, India - Sivaraj, Karthick; Mohan, Shanthakumar; Arockianathan, Samson; Jabamalainathan, Leona Princy; Jesudass, Beulahbah; Sanjay, Parihar (Therya Notes, 2025)
Melanism, the dominance of dark brown eumelanin over pheomelanin, is a rare condition in the Northern Red Muntjac (Muntiacus vaginalis) in India, resulting in a markedly darker pelage. This study reports a rare case of melanism in the Northern Red Muntjac in the Upper Nilgiris, Tamil Nadu. On March 5, 2024, we observed two muntjacs feeding in an invasive species eradication area in Kottagiri, one of which exhibited a distinctive dark brown, nearly black coloration, indicating melanism. This is one of only six recorded instances of melanism in this species in India. The Nilgiris’ high-altitude habitat, with dense vegetation and humid conditions, aligns with environments where other melanistic mammals have been reported, suggesting potential ecological factors at play. Further studies are warranted to explore the ecological and genetic bases of melanism in this species in the Nilgiris.